Democratization of Afghanistan and Karzai Regime - Mussarat Jabeen; Usman Shauket (Journal of Political Studies, 2019)
Afghanistan‟s dependency upon international economic and military assistance has brought international involvement and instruction in its internal affairs. The terrorist attacks of September 11, 2001 and subsequent war on terror not only damaged the very foundation of democracy, but also exposed the intentions of the US and its allies, whose interests were focused to the elimination of terrorism rather than the promotion of a political system to root out such evil permanently. The initial peace building efforts revealed the American intentions and installing a stable and cooperative regime in Afghanistan was not in lines with democracy. However, the Bush administration changed his role, realizing the American global commitment to democracy. After the fall of the Taliban regime, the UN made efforts to win the support for the ongoing peace process in Afghanistan and the political development through Bonn Agreement. The agreement was planned to make arrangement among the victors rather than a peace settlement between the belligerents. Humid Karzai was chosen as the head of the Interim Administration and later won the presidential election consecutively in 2004 and 2009. The Karzai administration violated the election procedure to secure its votes, accommodating the powerful armed groups. The Loya Jirga confirmed its support for American priorities, creating doubts about its legitimacy, bulldozing the expectations of the people for a healthy democratic setting in Afghanistan. The most serious question was the type of government as the ethnic minorities, consisting more than 50 percent of the population, wanted parliamentary system, whereas the US showed its inclination towards the presidential system. Elections were labeled independent, but some basic elements of democratic traditions were ignored as the political parties were sidelined, which produced a fragmented and weak legislature. Here the question is about the process of democratization of Afghanistan, whether the President Karzai regime adopted a right direction for true democratic setup, making incremental measures or molded the system as per interests and requirements in the name of security? After reviewing the available literature, the paper has hypothesized that the Karzai regime has not projected itself as a true elected representative of the people, but with the impression of the devotee of American interests in Afghanistan. The objective of the study is to look into the tenure of President Hamid Karzai and his regime‟s effort to democratize the state. Being a tribal society, the process of democratization was a new experience in Afghanistan, but the US and its allies ignored the culture, traditions and ethnic composition while launching Western liberal democracy. They forgot that the countries, which opt to be democratized can show performance if the system is assimilated to its traditions. The study is to explore the process of democratization in Afghanistan, reviewing the role of the regime. Both qualitative and descriptive methods have been used for analyzing the data.